"Workplace Physical Activity Program" (WOPAP) study protocol: a four-arm randomized controlled trial on preventing burnout and promoting vigor - Clément Ginoux; Sandrine Isoard-Gautheur; Philippe Sarrazin (BMC, 2019)
Abstract Background WOPAP is a theoretically-grounded workplace physical activity intervention that aims to reduce work-related burnout and to improve vigor at work and other work-related outcomes. Using a randomized controlled trial, we investigate whether a 10-week program including two Nordic walking sessions per week is effective in improving employee well-being at work, in comparison with another attractive leisure activity (Theatre condition) or a waiting list control condition. The design of the study makes it possible to test the effect on burnout and vigor of the instructor's style during physical activity (i.e., traditional vs. need-supportive style). Finally, this study is also interested in several possible psychological (i.e., detachment, relaxation, mastery, control, relatedness, and positive affects experiences) and physiological (i.e., cardiorespiratory fitness) mechanisms through which the practice of physical activity in the intervention could influence burnout and vigor. Methods Employees of the authors' University (N = 140) will be recruited via email, leaflets, and posters. Participants will be randomized to one of the four arms of the trial: (1) Physical Activity Traditional Style, (2) Physical Activity Need-Supportive Style, (3) Theatre condition, and (4) Waiting List Control. The experimental phase will last 10 weeks, followed by a six-month follow-up. During the ten weeks of the intervention, all groups - except the waiting list control - will carry out two activity sessions per week. Primary outcomes are burnout and vigor, secondary outcomes are work motivation, job satisfaction, work performance and work ability. These variables will be assessed before and after the intervention, and at three and six months after the end of the intervention. Moreover, burnout, vigor, needs satisfaction at work and psychological mediators will be assessed weekly throughout the intervention period. Discussion If effective, this study will provide evidence for the promotion of workplace physical activity interventions including a need-supportive climate to improve employee well-being. Results could be used to design new research protocols, but also to implement more efficient programs in the workplace. Trial registration ISRCTN12725337. Registered 21 March 2018. Registered retrospectively.